Cohort profile: Creation of an E-cohort to Address the Evaluation of Population Secondary Prevention Quality and Outcomes Post-Stroke (ESP-QOPS) in Wales - King, Daniel; Ellins, Elizabeth; Evans, Hywel; Evans, Nicholas; Gravenor, Michael; Halcox, Julian; Hewitt, Jonathan; Krishnan, Manju; McDonnell, Barry; Stone, Keeron; Harris, Daniel; Akbari, Ashley (International Journal of Population Data Science, 2026)
Purpose Secondary prevention of stroke requires effective cardiovascular risk factor (RF) management, including blood pressure control, lipid lowering treatment and antithrombotic therapy to reduce the risk of recurrent stroke. Optimal management of risk factors is challenging in older, frailer people, who also have worse outcomes after a stroke. There is limited evidence evaluating secondary prevention quality and outcomes in frail populations. To understand the trends (and factors associated with inequity) in the provision of RF management we developed the `Evaluation of Population Secondary Prevention Quality and Outcomes Post-Stroke (ESP-QOPS) in Wales' e-cohort. The aims of this project include describing (i) the provision of post-stroke evidence-based risk factor management (ii) trends in frailty and outcomes, and (iii) evaluating the impact of suboptimal risk factor provision on adverse outcomes stratified by frailty status. Participants We identified 71,696 patients with a first recorded stroke diagnosis in primary or secondary care between 2010-2023 in Wales. Findings to Date The incidence of stroke gradually increased from 4,968 to 5,391 patients per year between 2010-2023, with 70% of diagnoses made in the secondary care setting. Of diagnoses made in primary care, less than 20% were subsequently admitted to secondary care.